Penguatan Pendidikan Karakter Religius Melalui Kegiatan Ekstrakurikuler Keagamaan Di SMK Negeri Rembang Pasuruan - Mochamad Fajrin (Ta'limDiniyah: Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2023)
Religious character education is important for balanced personal development. Rembang State Vocational School has the responsibility to develop students' religious character. This research aims to analyze the strategies and implications of religious extracurricular activities in strengthening students' religious character. The research method is a case study with data from observation, interviews and documentation. The results show that strategies such as group discussions, Tadarus Al-Qur'an, Istighosah, and Al-Banjari shape student character. PAI teachers and extracurricular coaches play an important role. The implication is the formation of a character of responsibility, empathy, strong morals, and creating a harmonious school environment. This religious character helps students face challenges with confidence and better decision-making abilities.